Conversations with Mahathir Mohamad Doctor M : operation Malaysia - Plate, Tom (Giants of Asia, 2011)
He began his professional career as a family physician but wound up prescribing innovative political medicines for the entire nation that remain controversial even today. Was he exactly the bold and fearless policy doctor that the troubled body politic of Malaysia needed? Or was he just another mendacious mediocrity with a record of persistent misdiagnoses, phony remedies and self-serving justifications? Only history's judgment can offer the final verdict but Dr Mahathir himself is in no doubt. In a riveting series of unprecedented conversations, Malaysia's most famous former prime minister reveals to American journalist and author Tom Plate a panoramic panoply of views on governing, on Islam, on Jews, on the West and on Malays that are striking in historical sweep and contemporary relevance.